Logical Reasoning With Diagrams 1996
DOI: 10.1093/oso/9780195104271.003.0010
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Model Theory of Venn Diagrams

Abstract: One of the goals of logical analysis is to construct mathematical models of various practices of deductive inference. Traditionally, this is done by means of giving semantics and rules of inference for carefully specified formal languages. While this has proved to be an extremely fruitful line of analysis, some facets of actual inference are not accurately modeled by these techniques. The example we have in mind concerns the diversity of types of external representations employed in actual deductive reasoning.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A paradigmatic example of a formal diagrammatic logical system supporting syllogistic reasoning is the system VENN in [17] and [6], which is based on the Venn-Peirce diagrams, see also [7]. Here we briefly describe VENN by recalling its diagrammatic syntactic primitives and its rules of inference.…”
Section: Syllogistic Reasoning With Diagramsmentioning
confidence: 99%
“…A paradigmatic example of a formal diagrammatic logical system supporting syllogistic reasoning is the system VENN in [17] and [6], which is based on the Venn-Peirce diagrams, see also [7]. Here we briefly describe VENN by recalling its diagrammatic syntactic primitives and its rules of inference.…”
Section: Syllogistic Reasoning With Diagramsmentioning
confidence: 99%
“…False discovery rate (FDR) correction by Benjamini-Hochberg method [44] of the uncorrected p-values was performed using the SDM FDR online calculator [91]. The VENN DIAGRAMS tool [92] was used for comparing gene/miRNA lists.…”
Section: Discussionmentioning
confidence: 99%
“…It is based on a modification of the Venn-Peirce diagrams that returns to shading to represent empty regions and uses ⊗sequences to indicate existential import in them. See also [49], [24] and [26]. The Venn-I diagrams for the four categorical propositions are…”
Section: Contextualizationmentioning
confidence: 99%
“…Returning on the handling of inconsistency, we have observed that in GDS an imposed constraint for consistency does not permit the unification of two inconsistent EUL diagrams. In other systems a linguistic sign such as ⊥ is introduced for the purpose, see [62,26,33]. In SYLL, the inconsistency of two diagrams such as A ← • → B, A → • ← B, for instance, is provable:…”
Section: S P Xmentioning
confidence: 99%